Pollen morphology of Eremogone (Caryophyllaceae) in Türkiye - Tokuşoğlu, Kader Varlik; Armağan Meti̇n; Bülbül Ali̇ Savaş (Phytotaxa, 2024)
The palynological characters of 17 taxa belonging to genus Eremogone Fenzl (Caryophyllaceae) from Türkiye were examined using light microscopy and scanning electron microscopy. Eremogone pollen in Türkiye is found to have an average size of 31.31 μm (26.62‒36.65 μm), pore sizes ranging from 6.52 to 9.24 μm, inter-pore distances ranging from 9.07 to 12.57 μm, pore numbers varying from 5 to 14 and 5‒30 nanoechini distributed in an area of 10 × 10 µm. The ornamentation was identified as nanoperforate, nanoechinate, or nanofaveolate surface elements in various combinations. Clustering analysis and Principal Component Analyses do not show clear groups, although more similar taxa were brought together through the analysis of pollen micromorphological data rather, the nanoechinate base width, nanoechinate length, and pore diameter length are the most valuable variables for separating the examined taxa.